Molecular Detection of Antimicrobial Resistant Genes to Clarithromycin in Helicobacter pylori at Basrah, Iraq - Raneem A. Kareem; Lamyaa kadhim baqer; hayder mohsin jarullah (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The primary cause of gastritis and peptic ulcers, as well as gastric cancer and gastric mucosaassociated lymphoid tissue lymphoma, is the bacterium Helicobacter pylori. When an infection with H. pylori is discovered, eradication therapy should be started, and it is best if it is successful the first time. According to international standards, in some instances, medication susceptibility testing should be used to tailor treatment. The most widely used first-line treatment is still triple therapy, which combines a proton-pump inhibitor (PPI) with amoxicillin and clarithromycin (PPI-AC). This casecontrol study included 112 patients (55 males and 57 females), aged between 15 and 74, with a variety of gastritis symptoms, and 112 randomly chosen controls (59 males and 53 females), aged between 15 and 74, who were H. pylori negative. RUT and PCR were used for diagnosis of the bacteria. Realtime PCR was used to genotype two SNPs of the gene 23S rRNA, A2142G, and A2143G, which confer clarithromycin resistance. The rate of resistance to clarithromycin were 65.2% which consider high according to similar studies and this resistant appear that it was not associated with any of age, diabetes and smoking and it was result from point mutation in 23sRNA gene.